Sluggish Cognitive Tempo Predicts Academic Fluency, Beyond Contributions of Core Academic Skills, Attention, and Motor Speed. Issue 14 (December 2019) - Jacobson, Lisa A.; Mahone, E. Mark
Objective: Sluggish Cognitive Tempo (SCT) is a distinct behavioral phenotype characterized by such symptoms as being slow to complete tasks, appearing drowsy or sleepy, and lacking initiative. Subcomponents of SCT appear differentially associated with inattention symptoms and child outcomes. Much of the work in this area has examined associations between SCT symptoms and ratings of behavior; few studies have examined associations with child performance. Method: We examined associations between SCT and timed reading and math skills in 247 referred youth ( M age = 11.55, range = 6-20; 67.6% male), controlling for the untimed academic skills, inattention, and graphomotor speed. Results: SCT consistently predicted timed academic fluency, after controlling for other component skills, for both reading (SCT Δ R 2 = .039, p = .001) and math (Δ R 2 = .049, p = .001). Conclusion: Results provide initial evidence for the unique association of SCT with timed academic performance. Understanding associations of SCT with actual child performance may allow for greater specificity in targeting interventions to address speed of performance.